On the isospectrality of the scalar energy-dependent Schr odinger problems - Gülşen, Tüba; Panakhov, Etibar Sadi (My University, 2018)
In this study, we discuss the inverse spectral problem for the energy-dependent Schr odinger equation on a nite interval. We construct an isospectrality problem and obtain some relations between constants in boundary conditions of the problems that constitute isospectrality. Above all, we obtain degeneracy of K ( x;t )
Keywords: Matematik